2011
DOI: 10.2217/fca.11.83
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Therapy Versus Alternative Therapeutic Options for Prehypertension: an evidence-based Approach

Abstract: The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC-7) defines hypertension as systolic blood pressure (BP) ≥140 mmHg or diastolic BP ≥90 mmHg. The JNC-7 defines 'prehypertension' to include systolic BP values between 120 and 139 mmHg and diastolic BP values between 80 and 89 mmHg. Individuals with blood pressure in the prehypertension range are clearly at increased risk of developing hypertension in the future and have an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…3 In previous studies, pharmacological intervention reduced BP in prehypertensive subjects but the effect was associated with adverse side-effects of drugs. [23][24][25][26] Thus, a nonpharmacological intervention without any ill effects could be a good alternative. In our study, we observed a significant reduction in both systolic and diastolic BP in both the groups after 12 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…3 In previous studies, pharmacological intervention reduced BP in prehypertensive subjects but the effect was associated with adverse side-effects of drugs. [23][24][25][26] Thus, a nonpharmacological intervention without any ill effects could be a good alternative. In our study, we observed a significant reduction in both systolic and diastolic BP in both the groups after 12 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 169 individuals with prehypertension need to be treated with an antihypertensive drug for 4.3 years to prevent one stroke, indicating a relatively high number needed to treat in prehypertension [79]. Collectively, the pharmacological therapy of prehypertension remains a topic of lively discussion and debate [80][81][82][83].…”
Section: Attenuation or Delay Of Progressionmentioning
confidence: 99%